The Importance of Location for the Competitiveness of a Winter Sport Destination - Żemła, Michał; Żemła, Anna (Turyzm/Tourism, 2006)
The authors point to location as one of the basic factors affecting the competitiveness of a winter sports destination (understood as an area where skiers are provided with both basic and complementary services). The effect and significance of individual location factors as regards the functioning of a winter spoils destination have also been discussed.